Comparative characteristics of ethapolan and xanthan exopolysaccharides as agents for the increasing secondary oil extraction - Ivahniuk, Mykola; Pirog, Tatiana (My University, 2018)
The purpose of research – to compare the cost of nutrient mediums for obtaining culture fluids of Acinetobacter sp. IMB B-7005 and Xanthomonas campestris strains (xanthan gum producers) for its using in the secondary oil extraction. Materials and methods. Calculation of the culture fluid amount and the cost of nutrients for the ethapolan (producer – Acinetobacter sp. IMB B-7005) and xanthan (producers of Xanthomonas campestris strains) exopolysaccharides production as oil extraction agents for 262 oil wells of Oil and Gas Production Administration “Okhtyrkanaftogas” of JSC “Ukrnafta” was carried out taking into account the following parameters:4 times treatment per year of wells with the 15 m3 of EPS solution with its concentration 0,05%). Results and discussions. On the basis of the data on the concentration of synthesized polysaccharides by strainsproducer, the annual need for a culture fluid (545–1849 m3) was calculated for the treatment of wells of the OGPA “Okhtyrkanaftogas” and the amount of product per fermentation cycle according to selected technologies. Theoretical calculations have shown that costs for the nutrient medium preparing for Acinetobacter sp. IMB B-7005 culture fluid obtaining on waste sunflower oil after frying meat, necessary for increasing secondary oil extraction at “Okhtyrkanaftogas” wells in 1.8–5.4 times less than in the case of ethapolan obtaining on C2-C6 substrates, molasses or their mixtures. Comparison of nutrient medium cost for the preparation of ethapolan and the most famous polysaccharide xanthan obtained on molasses on technical glycerine was made. The cost of polysaccharide xanthan obtaining (in amount that would provide oil extraction in equivalent quantity like in case of ethapolan using) in 12.7–16.7 times higher compared to the ethapolan obtaining. Conclusion. Obtained results confirm the economic feasibility of the ethapolan synthesis on waste oil for the polysaccharide using in secondary oil production in comparison with the technologies for xanthan obtaining. Мета дослідження – порівняти вартість поживних середовищ для отримання культуральних рідин Acinetobacter sp. IMB B-7005 і штами Xanthomonas campestris (продуценти ксантанової камеді) для використання у вторинній екстракції олії. Матеріали та методи. Розрахунок кількості культуральної рідини та вартості поживних речовин для виробництва екзополісахаридів етаполану (продуцент – Acinetobacter sp. IMB B-7005) та ксантану (продуценти штамів Xanthomonas campestris) як нафтовидобувних агентів для 262 нафтових свердловин Нафтогазовидобувного управління. «Охтирканафтогаз» ВАТ «Укрнафта» проводилась з урахуванням наступних параметрів: 4-разова обробка на рік свердловин 15 м3 розчину ЕПС з концентрацією 0,05%). Результати та обговорення. На підставі даних про концентрацію синтезованих полісахаридів за штамами-продуцентами розраховано річну потребу культуральної рідини (545–1849 м3) для обробки свердловин НГПА «Охтирканафтогаз» та кількість продукту за цикл бродіння за до обраних технологій. Теоретичні розрахунки показали, що витрати на приготування живильного середовища для Acinetobacter sp. Отримання культуральної рідини ІМБ В-7005 на відпрацьованій соняшниковій олії після смаження м’яса, необхідної для збільшення вторинного видобутку нафти на свердловинах «Охтирканафтогаз» в 1,8–5,4 рази менше, ніж при отриманні етаполану на субстратах С2-С6, мелясі або їх сумішах. Проведено порівняння вартості живильного середовища для приготування етаполану та найвідомішого полісахариду ксантану, отриманого на мелясі на технічному гліцерині. Вартість одержання полісахариду ксантану (у кількості, яка б забезпечила екстрагування нафти в еквівалентній кількості, як при використанні етаполану) у 12,7–16,7 разів вища порівняно з одержанням етаполану. Висновок. Отримані результати підтверджують економічну доцільність синтезу етаполану на відпрацьованих оліях для використання полісахариду у вторинному виробництві олії порівняно з технологіями отримання ксантану.
Keywords: екзополісахарид; культивування; олія; кафедра біотехнології і мікробіології; Acinetobacter sp. ІМВ В-7005; Xanthomonas campestris; exopolysaccharide; cultivation; oil